Brooklyn three - Boyle, Thomas (New York : Viking Penguin Inc., 1991)
Detective Francis DeSales, head of the Brooklyn Violence Task Force, investigates a shooting at a political rally for New York's first Black mayoral candidate, a search that takes him from one end of Brooklyn to another in pursuit of a sociopathic weapons enthusiast.
Keywords: MYSTERY -- THRILLER -- FICTION